2017
DOI: 10.1089/jwh.2016.5771
|View full text |Cite
|
Sign up to set email alerts
|

Gender Differences in Outpatient Utilization: A Pooled Analysis of Data from the Korea Health Panel

Abstract: Unlike males, females with higher household incomes used outpatient services more. This suggests that females are at greater risk of medical inequality based on economic circumstances.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
13
1

Year Published

2018
2018
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(14 citation statements)
references
References 53 publications
(59 reference statements)
0
13
1
Order By: Relevance
“…These results may be due to differences in healthcare utilization between men and women in Korea. Although oldest-old women with less severe conditions use more medical resources than men with the same conditions, they tend to use intensive services less ( Noh et al, 2017 ). In rural areas, oldest-old women have higher untreated rates for acute diseases, fewer hospital treatments, and shorter hospital stays ( Shin et al, 2009 ).…”
Section: Discussionmentioning
confidence: 99%
“…These results may be due to differences in healthcare utilization between men and women in Korea. Although oldest-old women with less severe conditions use more medical resources than men with the same conditions, they tend to use intensive services less ( Noh et al, 2017 ). In rural areas, oldest-old women have higher untreated rates for acute diseases, fewer hospital treatments, and shorter hospital stays ( Shin et al, 2009 ).…”
Section: Discussionmentioning
confidence: 99%
“…Interactions were noted, whereby the association between DOAC versus warfarin usage and healthcare utilization was weaker in patients with VTE who were older and female. Women [34][35][36][37] and older individuals 37,38 have greater healthcare utilization than their male and younger counterparts. The simplest explanation for the weaker associations in women and older individuals is that these individuals have greater healthcare utilization for reasons independent of their VTE events and treatment, which may mute differences in healthcare utilization specifically related to the OAC prescribed.…”
Section: Discussionmentioning
confidence: 99%
“…The possible reasons could be that apart from family planning services, most CHPS services such as ANC, CWC, PNC, and skilled delivery, are female-focused. Additionally, research has shown that females by nature exhibit better health-seeking behaviour than males and this may be due to gender role differentiations including social class, education, and vulnerability to ill-health [28].…”
Section: Discussionmentioning
confidence: 99%
“…Our findings show that NHIS subscribers were more likely to utilise CHPS services than non-subscribers. This might be due to the financial protection which the scheme offers its subscribers [ 28 , 29 , 30 ]. This is because once subscribers pay affordable annual premiums, they can utilise health services covered by the scheme without paying anything at the point of service delivery [ 26 , 29 ].…”
Section: Discussionmentioning
confidence: 99%